Notes on the genus Cynophalla (Capparaceae) and the description of C. amazonica, a new species from Bolivia and Brazil - Cornejo, Xavier; Luber, Jaquelini; Iltis, Hugh H. (Phytotaxa, 2020)
The genus Cynophalla (Capparaceae) is commented, and Cynophalla amazonica, a new species from Brazil and Bolivia, is described, illustrated and its morphological similarities with the closely related C. flexuosa are discussed. The conservation status of Cynophalla amazonica is assessed as Least Concern.